DAMPAK KEMISKINAN KOTA TERHADAP PERUMAHAN DAN PERMUKIMAN DI KOTA BESAR INDONESIA - Ardiansyah, Adi (TERAS)
Urban policy will greatly impact on different population groups because these people are poor, although far from being a homogenous group but have the need and opportunity that is different from other groups in town.Â Characteristics of poor people living varies in every place, in accordance with the income derived is the starting point to test objects that will make adjustments for the individual within the scope of the city. Some of them are as follows: The first condition of the environment and health in different groups. The portrayal of high-risk living conditions is the key to understanding the problem of poverty. Both income and expenditure pattern of the group. This pattern would support the development of the town not only to those who are rich but will not doubt the poor.Â The third relative risk reduction of different groups in the city. One of the government policies, especially in urban areas, there is a policy that the city manager or urban areas, especially for dealing with problems and the performance of each city, where the Indonesian government has issued stating that Indonesias national development is essentially Whole Human Development, contained in national development objectives which the statement has the features are: first, to have a harmonious relationship with his god. Second, the harmony of human relationships with the community. Third, the built environment we must consider the human relationship with nature.Â